(untitled) (Journal of Engineering, 2013)
In this study, the electro-hydraulic servo system for speed control of fixed displacement hydraulic motor using proportional valve and (PID) controller is investigated theoretically ,experimentally and simulation . The theoretical part includes the derivation of the nonlinear mathematical model equation of (valve – motor ) combination system and the derivation of the transfer function for the complete hydraulic system , the stability test of the system during the operation through the transfer function using MATLAB package V7.1 have been done. An experimental part includes design and built hydraulic test rig and simple PID controller .The best PID gains have been calculated experimentally and simulation, speed control performance tests for the system at different thermal conditions for hydraulic oil have been done , Simulation analysis for (EHSS) using Automation Studio package V5.2 have been done . Comparison was made between experimental work and simulation work .The experimental results show good performance for (EHSS) using simple (PID) controller at hydraulic oil temperature around (60 – 70 ) and good speed response and performance for hydraulic motor with constant rotation speed (700) rpm with different load disturbance applied on the hydraulic motor .